Harry Potter and the chamber of secrets - Rowling, J. K.; Dale, Jim. (New York : Listening Library, 1999)
When the Chamber of Secrets is opened again at the HogwartsSchool for Witchcraft and Wizardry, second-year student Harry Potter finds himself in danger from a dark power that has once more been released on the school.
Unabridged.
Compact discs.
Sequel to: Harry Potter and the sorcerer's stone.
Sequel: Harry Potter and the prisoner of Azkaban.
Statement of responsibility from container.
Read by Jim Dale.
Keywords: Potter, Harry -- (Fictitious character) -- Juvenile fiction; Wizards -- Juvenile fiction; Magic -- Juvenile fiction. -- General books; Schools -- Juvenile fiction; Granger, Hermione (Fictitious character) -- Juvenile fiction; Weasley, Ron (Fictitious character) -- Juvenile fiction; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Juvenile fiction; England -- Juvenile fiction; Compact discs